Perbandingan Keaktifan dan Hasil Belajar Matematika Pada Penerapan Model Pembelajaran Kooperatif Tipe NHT dan TSTS - Nur Qalbi Tayibu (CV. Insight Publisher, 2024)
This research is experimental research with the aim of to determine the activeness and learning outcomes of students in mathematics before and after implementing the NHT and TSTS type cooperative learning models, to find out whether there is a difference between student activity and learning outcomes when implementing the NHT type cooperative learning model and the TSTS type, The design is a pretest-posttest design. The population is all class XI students of SMK YAPIKA Makassar. The sampling technique is total sampling. Based on the results of data analysis, the average mathematics learning achievement test scores before and after being taught with the NHT model were 64.90 and 83.00 with a standard deviation of 8.656 and 6.017. It can be seen that there is a significant increase in student learning outcomes in the high category, as seen from g>0.70, namely g=0.73 and the standard deviation is 0.785. The average test scores for mathematics learning outcomes before and after being taught using the TSTS model were 66.03 and 83.62 with standard deviations of 8.139 and 6.472. It can be seen that there is a significant increase in student learning outcomes in the high category, as seen from g>0.70, namely g=0.86 and the standard deviation is 0.743. Student learning activeness in the NHT and TSTS type cooperative learning models is in the high category. The results of inferential statistical analysis obtained a significant value of 0.520>0.05, so H0 was accepted. It was concluded that there was no significant difference in increasing student learning outcomes when implementing the NHT type cooperative learning model with TSTS